Enhancing the Implementation of Buddhist Pancasila Values in Religious Education at Atisa Dipamkara Elementary School, Tangerang - Okiyah, Okiyah; Sulani, Puji; Sugianto, Sugianto (Jurnal Pendidikan, Sains Sosial, dan Agama, 2025)
This study aims to analyze the strengthening of Buddhist Pancasila values in the context of Buddhist Religious Education at Atisa Dipamkara Tangerang Elementary School. This qualitative research employed a comprehensive approach, including interviews, observations, and document analysis for data collection, utilizing instruments such as interview guides, observation protocols, and documentation checklists. Data were meticulously analyzed using Miles, Huberman, and Saldaña's interactive model, which involves data collection, condensation, display, and conclusion/verification to address the research questions. The findings indicate that teachers internalize Buddhist Pancasila values through various methods, including teaching, reminding, reinforcing, habituating, emphasizing, modelling, and applying these values. These values encompassing compassion, love, helping others, non-violence, honesty, responsibility, gratitude, respect for self and others, admitting mistakes, refraining from defamation, maintaining focus, appropriate interactions with the opposite sex, and moderation in eating and drinking. The internalization of these values significantly influences students' character development, particularly in areas such as discipline, compassion, and respect for others, instilling confidence in the validity of the research findings. This research provides robust evidence of the impact of implementing Buddhist Pancasila values on students' character development, with practical implications for educators, researchers, and policymakers in the field of religious education and character development.